A preliminary study on the possibility of fermented pineapple peel residue partially replacing whole corn silage in feeding Chuanzhong black goats - Yang, Chuang; Zhao, Weiran; Tian, Hanchen; Wang, Mingyue; Gao, Chongya; Guo, Yongqing; Sun, Baoli (Frontiers in Microbiology, 2022)
This study aims to assess the effects of the partial replacement of whole corn silage (WCS) with fermented pineapple peel residue (FPPR) on growth, serological parameters, muscle quality, rumen microorganisms, and fecal microorganisms. A total of 24 Chuanzhong black goats weighing 10.23 ± 1.42 kg were evaluated in a randomized complete trial design in accordance with the following treatments: (1) 0% FPPR in the diet, (2) 25% FPPR in the diet, and (3) 50% FPPR in the diet. In goats, the partial substitution of FPPR for WCS increased the abundance of probiotics, such as Blautia, Butyrivibrio fibrisolvens, and Ruminococcus albus, and did not exert significant effects on overall serological parameters and muscle quality. In conclusion, the partial substitution of FPPR for WCS in the diet did no